DISHARMONI REGULASI HGB DI IKN YANG MENGAKIBATKAN KETIDAKPASTIAN HUKUM DAN KETIDAKADILAN - Sahala MPH Siahaan; Irene Eka Sihombing (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Abstract: The development of the Indonesian Capital City (IKN) requires land legal instruments that provide certainty and justice. The Right to Build (HGB) are a crucial instrument in land provision, but their regulation faces disharmony between the Basic Agrarian Law (UUPA), PP No. 40/1996, PP No. 18/2021, the IKN Law, and and their derivative regulations. This disharmony creates legal uncertainty, particularly for investment and injustice for the community and land management in the IKN. This study aims to analyze the HGB regulations in the Indonesian Land Law system and identify the sources of uncertainty in the regulations regarding HGB in the IKN. Using normative legal research methods with a descriptive analytical nature, this study compares laws and regulations. Data were obtained through literature review and analyzed qualitatively. The results show disharmony in regulations regarding the HGB term, the authority to grant rights, and the position of the IKN Authority. This condition increases the risk of legal uncertainty for investors and has the potential to cause injustice to the community. Therefore, regulatory harmonization is needed to ensure the effective development of the IKN and provide legal certainty and justice for all parties.Keywords: HGB, IKN, Disharmony of Regulation, Legal Certainty, Agrarian Law